Illuminating the Effect of the Local Environment on the Performance of Organic Sunscreens: Insights From Laser Spectroscopy of Isolated Molecules and Complexes - Wong, Natalie G. K.; Dessent, Caroline E. H. (Frontiers in Chemistry, 2022)
Sunscreens are essential for protecting the skin from UV radiation, but significant questions remain about the fundamental molecular-level processes by which they operate. In this mini review, we provide an overview of recent advanced laser spectroscopic studies that have probed how the local, chemical environment of an organic sunscreen affects its performance. We highlight experiments where UV laser spectroscopy has been performed on isolated gas-phase sunscreen molecules and complexes. These experiments reveal how pH, alkali metal cation binding, and solvation perturb the electronic structures of sunscreen molecules, and hence their non-radiative decay pathways. A better understanding of how these interactions impact on the performance of individual sunscreens will inform the rational design of future sunscreens and their optimum formulations.